Estilos de afrontamiento ante el retorno a clases presenciales de un estudiante de la ESPOL - Sanchez Pluas, Cristopher Alexis (2022)
The return to classes and stress are problems present today, both consequences of the confinement caused by the pandemic of yesteryear, worldwide, just as preventive measures were taken, in the same way measures were taken for the return to classes, which it was presumed that it would not manifest complications at a social level, the reality is that the stress levels of the student population increased, due to the fact that they lacked the resilience to face the situations and challenges that are present in the academic field. That is why the case presented shows the incidence of stress in coping with the return to face-to-face classes of a civil engineering student, in which it is observed that he develops active coping strategies, that is, the resources come from himself (knowledge, experience, technique and methodology) when facing academic challenges (homework, essays, presentations, etc.). Although a few weeks ago it was enough to cope with them, currently the level of stress exceeds the coping capacity, therefore, the use of other types of coping is proposed in this study as a proposal, in order to prevent stress from not knowing how to respond, adds to the stress of academic activities, therefore it is concluded that there was congruence between what was studied about coping and returning to classes, with the personal history of the patient, not only in the environmental dimension, but also in how this was affected psychologically, emotionally and behaviorally.